Reproductive skew in cooperative breeding: Environmental variability, antagonistic selection, choice, and control. Issue 18 (4th September 2019) - Nonacs, Peter
Abstract: A multitude of factors may determine reproductive skew among cooperative breeders. One explanation, derived from inclusive fitness theory, is that groups can partition reproduction such that subordinates do at least as well as noncooperative solitary individuals. The majority of recent data, however, fails to support this prediction; possibly because inclusive fitness models cannot easily incorporate multiple factors simultaneously to predict skew. Notable omissions are antagonistic selection (across generations, genes will be in both dominant and subordinate bodies), constraints on the number of sites suitable for successful reproduction, choice in which group an individual might join, and within‐group control or suppression of competition. All of these factors and more are explored through agent‐based evolutionary simulations. The results suggest the primary drivers for the initial evolution of cooperative breeding may be a combination of limited suitable sites, choice across those sites, and parental manipulation of offspring into helping roles. Antagonistic selection may be important when subordinates are more frequent than dominants. Kinship matters, but its main effect may be in offspring being available for manipulation while unrelated individuals are not. The greater flexibility of evolutionary simulations allows the incorporation of species‐specific life histories and ecological constraints to better predict sociobiology. Abstract : This work examines the evolution of cooperation through a genetic simulations that incorporate ecological and life history constraints. The results show how previously static inclusive fitness models can dynamically expand to consider more realistic conditions.